Phylogenetic analysis and genotypic characterization of coagulase-negative Staphylococcus aureus isolates from sheep subclinical mastitis milk in Nineveh governorate, Iraq - Karam M. Abdulrazzaq; Ayman H, Taha; Omar H. Sheet (Iraqi Journal of Veterinary Sciences, 2025)
Staphylococcus (S.) aureus is a major microorganism that causes a subclinical inflammation of the mammary glands in animals. The current study aimed to isolate and identify coagulase-negative Staphylococcus aureus (CNSA) in non-clinical inflammation of the mammary glands and to detect the nuc, mecA, clfA, clfB, coa, and 16S rRNA genes, along with constructing a phylogenetic tree. Samples of the non-clinical milk of sixty sheep were gathered from various regions. The standard bacteriological methods were used to isolate and identify the CNSA isolates, while the PCR method was utilized to confirm and find the specific genes. Based on the results, the occurrence rate of CNSA was initiated in sheep asymptomatic mastitis at a proportion of 11.7 (7/60), and a high prevalence of CNSA in non-clinical inflammation of the mammary glands of sheep was 20% (3/15) in the Al-Nimrod district. Nevertheless, Hawe Al-Kaneisa doesn't have any isolated CNSA. The results of the PCR method showed that all CNSA isolates possessed the nuc gene 100 (7/7). Additionally, all isolates were methicillin-resistant coagulase-negative S. aureus, which has the mec A gene 100%, and they possessed the clfA, clfB, and 16S rRNA genes 100%. No one in CNSA has the coa gene. In addition, this study showed that only one of the gene profiles was 100%. According to the 16S rRNA gene, seven unique strains of S. aureus sequences have been registered in GenBank. The phylogenetic tree showed the relationship between the CNSA isolated in this study and the relationship with the CNSA isolates worldwide.